The potential contribution of bread buns fortified with β-carotene–rich sweet potato in Central Mozambique - Low, Jan W.; Van Jaarsveld, P.J. (SAGE Publications, 2008)
Abstract Background Orange-fleshed sweet potato is an efficacious source of vitamin A. Substituting wheat flour with orange-fleshed sweet potato in processed products could reduce foreign exchange outlays, create new markets for producers, and result in increased vitamin A consumption among consumers provided there is adequate retention of β-carotene during processing. Objective To explore whether substituting 38% of wheat flour (by weight) in bread buns (“golden bread”) with boiled and mashed orange-fleshed sweet potato from fresh roots or rehydrated chips would produce economically viable β-carotene–rich products acceptable to Mozambican rural consumers. Methods Modified local recipes maximized sweet potato content within the limits of consumer acceptability. Sensitivity analysis determined parameters underlying economic viability. Two samples each of buns from five varieties of orange-fleshed sweet potato were analyzed for β-carotene content. Processed products with at least 15 μg/g product of trans-β-carotene were considered good sources of vitamin A. Results Golden bread made from fresh roots of medium-intensity orange-fleshed sweet potato varieties met the good source criterion, but bread from lighter-intensity sweet potato varieties did not. Bread from rehydrated dried chips was not economically viable. Consumers strongly preferred golden bread over pure wheat flour bread because of its heavier texture and attractive appearance. The ratio of the price of wheat flour to that of raw sweet potato root varied from 3.1 to 3.5 among the bakers, whose increase in profit margins ranged from 54% to 92%. Conclusions Golden bread is a good source of β-carotene and is economically viable when the price ratio of wheat flour to raw orange-fleshed sweet potato root is at least 1.5. Widespread adoption during sweet potato harvesting periods is feasible; year-round availability requires storage.